Intramammary Tumor Location and Ipsilateral Lymphatic Spread in Early Breast Cancer Patients Using One-Step Nucleic Acid Amplification (OSNA) Assay - Mariana Robalo Cordeiro; Inês Gante; Daniela David; Ana Gomes; Margarida Figueiredo-Dias (The Breast Journal, 2024)
Establishing an accurate prognosis for women diagnosed with breast cancer (BC) is extremely challenging. Axillary lymph node (ALN) evaluation is considered of major prognostic value. The one-step nucleic acid amplification (OSNA) assay is currently used for assessing axillary sentinel lymph node (SLN) status in BC. Additionally, total tumor load (TTL) may help predict further metastatic axillary involvement beyond the SLN. The prognostic value of primary BC location remains controversial due to lack of consensus on the biological differences among tumors at various sites. Evidence suggests that tumors in the internal quadrants (INLs) have worse prognosis compared to those in the external quadrants. Furthermore, ALN involvement is believed to be mainly associated with external quadrant tumors, mainly due to the lymphatic drainage system of the breast. This pilot observational study, despite lacking a control group and having a relatively small sample size, is the first to evaluate the potential relationship between primary BC location and ALN metastasis using the OSNA assay. A sample of consecutive BC patients undergoing axillary staging with the OSNA assay were included. Tumors were categorized into three groups based on primary location: external quadrants and axillary tail (EXL), INLs, and nipple and areola location (NAL). Although not statistically significant, the INL group exhibited a higher mean TTL. Additionally, no significant differences were observed between groups concerning SLN detection techniques, SLN status, number of metastatic SLN, or mean TTL. These findings support the use of the innovative tracer superparamagnetic iron oxide regardless of tumor site. This study underscores the importance of understanding the relationship between BC location and ALN status, which may improve prognostic stratification and targeted therapies based on tumor site. If these observations are confirmed in larger, multicentric studies, the potential conclusions may shift the paradigm of INL tumor treatment, significantly impacting clinical practice and research.